MicroRNA-204 (miR-204) (Science-Business eXchange, 2011)
Assessing the impact of control and prevention strategies on zoonotic diseases in human populations requires the use of formal modelling frameworks, integrating animal, environmental and human data. However, such quantitative "One Health" approaches to guide public health interventions are, to date, overlooked. Their implementation could be facilitated by improved access to epidemiological, demographic, and contact data on different hosts, by improved training of epidemiologists and modellers through relevant multidisciplinary research career paths, and finally by improving institutional support for better visibility.